Praetorian - Scarrow, Simon (Scarrow, Simon. Roman Legion series, 2011)
The thrilling Roman adventure from the author of THE LEGION and THE GLADIATOR. The city of Rome in AD 50 is a dangerous place. Treachery lurks on every corner, and a shadowy Republican movement, 'the Liberators', has spread its tentacles wide. It is feared that the heart of the latest plot lies in the ranks of the Praetorian Guard. Uncertain of whom he can trust, the Imperial Secretary Narcissus summons to Rome two courageous men guaranteed to be loyal to the grave: army veterans Prefect Cato and Centurion Macro.